2009
DOI: 10.1073/pnas.0901615106
|View full text |Cite
|
Sign up to set email alerts
|

Interareal coordination of columnar architectures during visual cortical development

Abstract: The formation of cortical columns is often conceptualized as a local process in which synaptic microcircuits confined to the volume of the emerging column are established and selectively refined. Many neurons, however, while wiring up locally are simultaneously building macroscopic circuits spanning widely distributed brain regions, such as different cortical areas or the two brain hemispheres. Thus, it is conceivable that interareal interactions shape the local column layout. Here we show that the columnar ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 69 publications
1
35
0
Order By: Relevance
“…Previous studies using 2-deoxyglucose showed that the size of isoorientation domains in area 17 was smaller than that in area 18 in cats (Lowel et al, 1987;Kaschube et al, 2009). Here, we found that the periodicity of orientation arrangements, which is inversely proportional to the iso-orientation domain size, gradually increased as the stimulus spatial frequency increased.…”
Section: Size Of Orientation Domainssupporting
confidence: 60%
See 1 more Smart Citation
“…Previous studies using 2-deoxyglucose showed that the size of isoorientation domains in area 17 was smaller than that in area 18 in cats (Lowel et al, 1987;Kaschube et al, 2009). Here, we found that the periodicity of orientation arrangements, which is inversely proportional to the iso-orientation domain size, gradually increased as the stimulus spatial frequency increased.…”
Section: Size Of Orientation Domainssupporting
confidence: 60%
“…Previous studies using 2‐deoxyglucose showed that the size of iso‐orientation domains in area 17 was smaller than that in area 18 in cats (Lowel et al. , 1987; Kaschube et al. , 2009).…”
Section: Discussionmentioning
confidence: 82%
“…These requirements are consistent with the physiological action of nonlocal influences in the visual cortex (12, 25) but hard to reconcile with the notion that pinwheels are quasi-isolated local circuit elements. The relevant genes controlling their formation are thus expected to concern the regulation of lateral axon outgrowth and the setting of overall synaptic input balance (14, 25). Genetic or experimental perturbations that restrict neuronal interactions in the visual cortex to the range of an individual hypercolumn are predicted to induce the breakdown of spatially complex orientation maps into pinwheel sparse or crystal-like patterns.…”
mentioning
confidence: 84%
“…Tangential to the visual cortical layers, orientation preference changes smoothly and progressively [2] except at the centers of so-called pinwheels where neurons exhibiting the whole range of orientation preferences are located in close vicinity [2,3]. The progression of orientation preferences across the visual cortical surface (Orientation preference map, OPM) appears as organized by a semiregularly spaced system of pinwheels and adjacent columns preferring the same orientation over roughly a millimeter distance [4][5][6][7][8][9][10][11][12]. Most models for the emergence of OPMs during postnatal development assume that their layout is determined by intracortical mechanisms (e.g.…”
Section: Introductionmentioning
confidence: 99%